Pengaruh Pengalaman, Keahlian, Situasi Audit, Etika, dan Gender Terhadap Skeptisisme Profesional Auditor (Studi Empiris Pada KAP di Surakarta Dan Yogyakarta) - Adhitya, Jefry, Dra.Rina Trisnawati, Ak. MSi.,Ph.D (2015)
The purpose of this study was to determine the effect the experience, expertise, audit situations, ethics and gender on the auditor's professional skepticism case study on the hood in Surakarta and Yogyakarta. The study population was auditor who works at KAP Yogyakarta and Surakarta totaling 12 KAP . The research sample are 32 auditors from 6 KAP are willing to be the object of research . The sampling technique in this research is convenience sampling . Analysis of the data used is the classical assumption of normality test , multicoloniarity , and heteroscedasticity . As well as linear regression analysis . The results showed that: (1) Experience partially affect the Auditor Professional Skepticism at the 0.05 level, with sig. Experience Auditor 0.004 <0.05; (2) expertise in partially influence Auditor Professional Skepticism at the 0.05 level, with sig. Expertise Auditor 0.039 <0.05; (3) The situation Audit partially affect the Auditor Professional Skepticism at the 0.05 level, due to the sig. Situation Audit 0,040 <0.05; (4) The Auditor Ethics partially affect the Auditor Professional Skepticism at the 0.05 level, with sig. Auditor Ethics 0.039 <0.05; (5) Gender partially Auditor does not affect the Auditor Professional Skepticism at the 0.05 level, due to the sig. Gender 0.988> 0.05.